Symbolic Interaction between Teachers and Students in Fostering Effective Classroom Learning - Amelia, Rita; Misrawita, Misrawita; Januar, Januar (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
This study aims to examine the concept of symbolic interaction between teachers and students in the classroom learning process. The meaning of symbols in the context of education plays an important role in forming harmonious social relationships, increasing learning motivation, and strengthening students' self-identity. Teachers are seen not only as conveyors of knowledge, but also as social actors who create symbolic meanings that influence students' behavior and perceptions of the learning process. Symbolic interaction in the classroom occurs not only through verbal communication but also through nonverbal symbols, emphasizing the important role of technology and digital media in changing patterns of symbolic interaction in modern classrooms that present new symbols such as emojis, visual icons, and other forms of digital representation that also influence social meaning in learning. The study was conducted through an analysis of classical and contemporary literature relevant to symbolic interactionism theory, particularly the works of George Herbert Mead and Herbert Blumer, using a qualitative approach and library research methods. The main focus of this study is to analyze how symbols, meanings, and social communication processes between teachers and students contribute to the formation of meaningful learning experiences. The implications of this study can form the basis for the development of symbolic communication-based learning strategies that are adaptive to current social and educational technology changes. Overall, this study emphasizes that understanding symbolic interactions in learning is key to building effective, participatory, and humanistic educational communication.